INTEGRASI PENDEKATAN DEEP LEARNING DALAM KURIKULUM MERDEKA 2025 SEBAGAI STRATEGI TRANSFORMASI PEMBELAJARAN BERMAKNA DAN ADAPTIF DI INDONESIA - Siva Amelia, Chelomita; Gita Pramudia, Allysa; Juwita Sukmawati, Maharani; Zid, Muhammad (Jurnal Spasial, 2026)
The integration of Deep Learning approach into the Independent Curriculum 2025 is a crucial strategy for transforming education in Indonesia towards meaningful, adaptive, and contextual learning. This study employs a qualitative descriptive method with document and literature analysis, identifying that the success of Deep Learning implementation largely depends on human resource readiness and technological infrastructure. Findings indicate increased active student engagement and learning effectiveness through a model focusing on meaningful learning, mindful learning, and joyful learning. Major challenges such as technology access disparity and low digital literacy must be addressed to enhance national education quality and to prepare learners to face the global challenges of the 21st century